Secondary Prefaces and the Composition of Luke-Acts - Sterling, Gregory E. (New Testament studies, 2025)
In the first part of the twentieth century, Henry Cadbury argued for the unity of Luke and Acts and made the phrase Luke-Acts a standard expression in scholarship. While there have always been challenges, in recent decades the number of these has increased. One area that has not been adequately explored is the study of how ancients produced multi-scroll works. This study analyses two practices using four examples for each: two Hellenistic and two Jewish. The first is the practice of composing secondary prefaces for the second and subsequent scrolls in multi-scroll works. The purpose of the secondary preface was to create a link between the scrolls. The second is the practice of releasing a scroll when it was completed before the full complement of scrolls for the work was composed and ready for circulation. This essay suggests that Acts 1.1-2 is a secondary preface that binds Acts to Luke and that there is a gap in time between the release of Luke and the release of Acts, which helps to explain both their differences and their independent circulation in the early church. It is not an argument about genre since these practices were common in various genres. It is an argument that Luke and Acts cannot be separated from one another without ignoring ancient conventions.*